2020
DOI: 10.3390/su12052092
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge Modeling and the Analysis of Ancient Landslides Subjected to Reservoir Water Level Fluctuation

Abstract: Landslides are among the most severe natural hazards with significant impacts in human life and infrastructure. The Three Gorges Reservoir Area (TGRA) is vulnerable to landslides because of the geological environment and human activities. A centrifuge model test of a landslide with a planar sliding surface in the TGRA was conducted. Based on the multiple monitoring systems composed of a 3D laser scanner, pore water pressure transducers, particle image velocimetry and earth pressure sensors, multiphysical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The evolution and formation mechanism of three large-scale landslides in the Three Gorges Reservoir Area (TGRA) were thoroughly investigated, and it is found that many features associated with landslides were caused by slow, downslope gravitational processes before landslide failure [9]. The long-term deformation pattern of an ancient landslide with a planar sliding surface in the TGRA was found to be deeply connected with periodic fluctuations in the reservoir water level [10]. The failure of these landslides is strictly influenced by the increase in pore water pressure and the consequent reduction in mean effective stress and is considered a complex slope instability phenomenon since the landslides exhibit distinct kinematic characteristics during the failure, post-failure, and propagation stages [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The evolution and formation mechanism of three large-scale landslides in the Three Gorges Reservoir Area (TGRA) were thoroughly investigated, and it is found that many features associated with landslides were caused by slow, downslope gravitational processes before landslide failure [9]. The long-term deformation pattern of an ancient landslide with a planar sliding surface in the TGRA was found to be deeply connected with periodic fluctuations in the reservoir water level [10]. The failure of these landslides is strictly influenced by the increase in pore water pressure and the consequent reduction in mean effective stress and is considered a complex slope instability phenomenon since the landslides exhibit distinct kinematic characteristics during the failure, post-failure, and propagation stages [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…6). According to previous studies (Li et al, 2020a;Qian, 2016;, the dip angle of the DBI θ is usually lower than the internal friction angle ϕ in under-dip landslide. Thus, the whole DBI can be considered as the locked segment according to rigid limit equilibrium method.…”
Section: Problem Formulationmentioning
confidence: 86%
“…The DBI morphology is believed as a dominated factor for slope stability calculation and mitigation measures designs (Hu and Wang, 2010;Stout, 1971;Sun and Hu, 2016). The scientific literature contains many well-documented case histories for the relationship between DBI morphology and failure mechanisms (Tannant et al, 2017;Huang et al, 2015;Li et al, 2020a;Pan et al, 2016;Tang et al, 2020). However, surprisingly, works concerning the statistical analysis of the influence of different kinds of DBI morphology on dual-structure landslide stability in the TGR is rare.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 241 slopes have been selected for the statistical analysis of susceptibility to rockfalls. The selection of predisposing factors has been based on bibliographic criteria ( [58]), and particular attention has been granted when adding to the usual natural causes artificial factors that are characteristic of the anthropized environment of the roads, such as cuts, irrigation, extractive activity or clearing ( [59]; [60]; [61]). No factors related to precipitation or seismicity have been included, as they are not spatially discriminatory when working at large-scale.…”
Section: Development Of the Inventory Of The Slopes With Signs Of Effective Mobilizationmentioning
confidence: 99%
“…It is a multivariate statistical method that allows to predict the presence or absence of a given event according to the values of a set of starting indicators. The binomial logistic regression allows us to deduce an equation that establishes the underlying mathematical relationship between a dependent dichotomous variable, and a set of independent predictor variables ( [59]). For the analysis, variables of different nature and statistical expression (continuous or categorical, and with or without normal distribution) can be included.…”
Section: Evaluation Of the Effectiveness Of The Ws Modelmentioning
confidence: 99%